PENGARUH POLA KOMUNIKASI INTERAKSIONAL DAN KETELADANAN ORANGTUA TERHADAP PEMBENTUKAN KARAKTER REMAJA - Nursita, Yana; Sudiapermana, Elih (Comm-Edu (Community Education Journal), 2025)
This study reseacrh the influence of family interactional communication patterns and parental role modeling on children’s character development in the rural village of Tanjuang Bungo, West Sumatra. The research addresses the increasing concern about moral crises among adolescents in rural areas, where family dynamics play a critical role in shaping moral behavior. The study aimed to explore whether open communication and positive parental examples could mitigate these crises and promote stronger character development. A cross-sectional survey was conducted with 42 families, using structured questionnaires to measure communication patterns, parental role modeling, and children's character traits. Correlational and multiple regression analyses were employed to examine the relationships between these variables. The results indicated that both interactional communication and parental role modeling significantly contributed to children’s moral development. Open, two-way communication was strongly associated with better moral outcomes, and children who viewed their parents as positive role models demonstrated greater empathy, responsibility, and ethical behavior. These factors explained 48% of the variance in character development, highlighting the critical influence of family dynamics. The findings suggest that strengthening family communication and role modeling can improve character education in rural areas. This study contributes to the literature on family-based moral development and suggests further research in diverse rural contexts